From slave abuse to hate crime: the criminalization of racial violence in American history - Aaronson, Ely (Cambridge historical studies in American law and society, 2014)
Machine generated contents note: 1. Towards a historical and sociological analysis of the criminalization of racial violence; 2. Progressive criminalization at the heart of darkness?: The legal response to the victimization of slaves in the colonial and antebellum South; 3. 'Social equality is not a subject to be legislated upon': the rise and fall of federal pro-black criminalization policy, 1865-1909; 4. 'We bring it out in the open, where it can be seen and dealt with': campaigning for criminalization reform in the long civil rights movement, 1909-1968; 5. Criminalizing racial hatred, legitimizing racial inequality: hate-crime laws and the new politics of pro-black criminalization; 6. Conclusion: criminalization reform and egalitarian social change -- an uneasy relationship